ANALYSIS OF THE ROLE OF INTERNAL AUDITORS’ FUNCTION TOWARDS THE LENGTH OF AUDIT DELAY - Sri Astuti; Kusharyanti Kusharyanti (Journal of Economics, Business, and Accountancy Ventura, 2013)
The role of internal auditors’ function is very important. This research investigates the effect of the function and contribution of internal auditor on audit delay. Audit delay is measured by using the number of days between a firm’s fiscal yearend and the audit report date. In doing this analysis, this research used samples from 218 companies other than financial institutions listed on Indonesia Stock Exchange that published annual report at 2012. The method used was purposive sampling. The analysis was done by means of multiple regression, with dependent variable is audit delay and independent variables are of quality and contribution of internal auditor function. The results of this research show that there is no significant effect of quality and contribution of an internal auditor function in a firm on audit delay.